Comparison of Asmaul Husna and Benson Relaxation on Decreasing of Pain among Patients with Post Antebrachii Operated at Public Hospital Sidoarjo - Ika Puspita Sari; Dwikora Dwikora; Ninuk Dian Kurniawati (Alta Dharma Publisher, 2020)
Fractures are a breakdown of bone continuity caused by sudden and excessive force, which can be a beating, destruction, bending, twisting or withdrawl. Benson relaxation (RB) can reduce pain. The study aimed at examining the Effect Of Comparison Of Asmaul Husna Benson And Benson Relaxation On Pain Scale Decrease On Post Operation Patients Antebrachii Fractures In Hospital Sidoarjo. Methods: This study used a quasi-experimental, pre and post with a control group was applied in this study. two eight samples were recruited using nonprobability sampling type consecutive sampling and divided into 2 benson relaxation groups and asmaul husna distraction groups. Data analysis was performed and presented in descriptive statistics, and significant findings were computed using ANOVA t-test. Results: The results showed that the mean pain scale benson relaxation group downhill from 6,07 ± 2,20 to 3,29 ± 2,30 after the intervention. Meanwhile, the asmaul husna distraction group, the mean pain scale downhill from 5,29 ± 2,37 to 2,50 ± 1,40. The Anova t-test obtained a p-value of 0.000, indicating that there were significant differences in the decrease in anxiety level between the benson relaxation and the asmaul husna distraction group. Conclusion: Benson relaxation can reduce the pain scale better than asmaul husna benson in patients post-antebrachii fracture surgery in Sidoarjo Hospital. The nurse profession is expected to be able to use preoperative benson relaxation to decrease pain scale on post operation patients antebrachii fractures.